SUBTITUSION OF RPO TO SEASONING OIL AND ACCEPTABILITY AND FORTIFICATION POTENCY OF VITAMIN A TROUGH CHICKEN NOODLE - Lia Agustina; Budiyanto Budiyanto; Tuti Tutuarima (Jurnal Agroindustri, 2018)
ABSTRACTThis study aims to obtain the amount of RPO, ?-carotene content, increase of vitamin A availability after red palm oil was added to the seasoning. This research uses Completely Randomized Design (RAL) with one factorial that is RPO concentration (0%, 25%, 50%, 75% and 100%). The results showed that the content of ?-carotene in RPO was 348,23 ppm or equivalent to 28,44 ?g RE per gram, mie ayam seasoning with RPO 100% addition was the most favored and accepted chicken noodle condiment by consumer as a whole, by consuming 100% RPO can meet provitamin A requirements of 117.78 ?g RE (adult female) and RPO (Red Palm Oil), Chicken Noodle Seasoning.